2013
DOI: 10.1016/j.epsl.2012.12.039
|View full text |Cite
|
Sign up to set email alerts
|

A three-year time series of mineral dust deposits on the West African margin: Sedimentological and geochemical signatures and implications for interpretation of marine paleo-dust records

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
64
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 57 publications
12
64
1
1
Order By: Relevance
“…The observed occurrence of the minerals quartz, feldspar, mica, chlorite and calcite has also been described for the bulk size fraction of soil samples and dust samples collected in Mauritania (Schütz and Sebert, 1987). Palygorskite, mica and chlorite have also been detected by Skonieczny et al (2013) in the PM 30 size fraction of a 3-year time series of dust deposition at M'Bour, Senegal, more than 500 km south of Iwik, Mauritania. Smectite and kaolinite, which were absent in the Iwik samples, were the dominant minerals of the dust sampled at M'Bour (Skonieczny et al, 2013).…”
Section: Dust Mineralogical Compositionmentioning
confidence: 91%
See 3 more Smart Citations
“…The observed occurrence of the minerals quartz, feldspar, mica, chlorite and calcite has also been described for the bulk size fraction of soil samples and dust samples collected in Mauritania (Schütz and Sebert, 1987). Palygorskite, mica and chlorite have also been detected by Skonieczny et al (2013) in the PM 30 size fraction of a 3-year time series of dust deposition at M'Bour, Senegal, more than 500 km south of Iwik, Mauritania. Smectite and kaolinite, which were absent in the Iwik samples, were the dominant minerals of the dust sampled at M'Bour (Skonieczny et al, 2013).…”
Section: Dust Mineralogical Compositionmentioning
confidence: 91%
“…The particle size correlated to local surface wind speed suggesting the contribution of local dust (Kandler et al, 2009). In contrast, in coastal Senegal, dust is sourced from the Sahel during winter as shown by low illite / kaolinite (I / K) ratios and lower palygorskite contents as opposed to the summer samples, which were suggested to originate from the Sahara (Skonieczny et al, 2013). Further, the I / K ratio in dust sampled on the Cape Verde Islands showed that dust was derived from strongly varying sources: northwestern Sahara, central and southern Sahara, and the Sahel (Caquineau et al, 2002).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Although part of the carbonate fraction might also have a terrestrial provenance as transported, for instance, with Saharan dust (Chester et al, 1977;Correggiari et al, 1989;Rutten et al, 2000), this does not seem to be the case with the investigated samples. Like other aeolian particles, aeolian carbonates are typically better sorted than those formed in situ, as shown by a well-sorted unimodal distribution due to gravitational settling during atmospheric transport (Skonieczny et al, 2013). The predominance of very poorly sorted grain size distributions within the bulk sediment samples (Fig.…”
Section: Lithogenics and Carbonatementioning
confidence: 98%